PENGUATAN TENAGA PENDIDIK: UPAYA MEMINIMALISIR PROBLEMATIKA PENDIDIKAN NASIONAL - Ru’ung, Darius (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2021)
Several national education problems such as low HDI, limited facilities and infrastructure, national education, and the problem of teaching staff require national education stakeholders to immediately formulate a strategy to minimize the problem of national education, one of which is to strengthen educators, this is based on the dominance of the role and the function of educators in national education. Efforts to encourage educators include; (i) Competency Development for Educators, an educator to have pedagogic, personality, social and professional competencies. The competence of educator has a major contribution to ensuring a quality process in institutions at all levels of education, and (ii) improving the institutionalization of educators and teaching staff in producing more competitive educators. Institutional forms of educators include associations, cooperatives, MGMP and so on. The main elements of education are teachers, students, and the education system. These three things are interdependent, but the teacher's factor seems to be the most decisive in the success of education.